2006
DOI: 10.1369/jhc.6a7033.2006
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution of Ca2+-dependent Activator Protein for Secretion Family Members CAPS1 and CAPS2 in Mice

Abstract: The family of Ca2+-dependent activator proteins for secretion (CAPS) is involved in dense-core vesicle exocytosis. CAPS1/CADPS1 and CAPS2/CADPS2 have been identified in mammals. CAPS1 regulates catecholamine release from neuroendocrine cells, whereas CAPS2 is involved in the release of brain-derived neurotrophic factor and neurotrophin-3 from cerebellar granule cells. CAPS1 and CAPS2 are predominantly expressed in brain. Here we show the immunohistochemical localization of the CAPS family proteins in various m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…We have identified 42 probes that can be divided into two groups, those that seem to be increasingly downregulated with AD severity (CABP1 [235], [236], [237], [238], [239], [240], [241], [242], [243], CADPS2 [244], [245], [246], [247], [248], [249], COLQ [250], DMD [251], [252], [253], [254], [255], [256], ELOVL2 [257], FAIM2/LFG [258], [259], [260], [261], GABBR2 [262], [263], [264], [265], GRIA2/GLUR2 [266], [267], [268], [269], [270], [271], [272], [273], [274], [275], [276], [277], ITPR1 [278], [279], [280], [281], [282], [283], KIAA0528, LZTS1/FEZ1 [284], [285], NEFM, NRG1, NRXN1, NUFIP1 [286], [287], [288], PPT1 [289], [290], [291], [292], [293], [294], [295], [296], …”
Section: Resultsmentioning
confidence: 99%
“…We have identified 42 probes that can be divided into two groups, those that seem to be increasingly downregulated with AD severity (CABP1 [235], [236], [237], [238], [239], [240], [241], [242], [243], CADPS2 [244], [245], [246], [247], [248], [249], COLQ [250], DMD [251], [252], [253], [254], [255], [256], ELOVL2 [257], FAIM2/LFG [258], [259], [260], [261], GABBR2 [262], [263], [264], [265], GRIA2/GLUR2 [266], [267], [268], [269], [270], [271], [272], [273], [274], [275], [276], [277], ITPR1 [278], [279], [280], [281], [282], [283], KIAA0528, LZTS1/FEZ1 [284], [285], NEFM, NRG1, NRXN1, NUFIP1 [286], [287], [288], PPT1 [289], [290], [291], [292], [293], [294], [295], [296], …”
Section: Resultsmentioning
confidence: 99%
“…Immunoreactive bands corresponding to short isoforms (CAPS2d-f) were observed at low to undetectable protein levels in the mouse cerebellum (Figure 5B). In addition, the previous report showed that in non-neural tissue such as pituitary, lung, pancreas and kidney, only a 150 kDa band immunoreactive for CAPS2 was detected [15]. At the mRNA level, more reaction cycles and time were needed for the amplification of transcripts encoding the short isoforms by RT-PCR and for the colorimetric detection of transcripts by in situ hybridization, respectively, indicating that the expression levels of the genes encoding the short isoforms are very low.…”
Section: Resultsmentioning
confidence: 99%
“…Deletion of CAPS1 and CAPS2 in mice [134, 135] and cell cultures [136] severely impair catecholamine and glucose-stimulated-insulin release. However, the redundancy of CAPS1 and CAPS2 in tissue expression [137, 138] has not allowed researchers to precisely pinpoint their mechanism of action with the exception of the fact that both CAPS proteins bind to phosphatidylinositol 4,5-bisphosphate (PIP2), a phosphoinositide that has been shown to be required for priming [139]. Once the secretory vesicles are primed, a trigger is the only requirement to promote the fusion between the lipid bilayers of the vesicles and the plasma membrane.…”
Section: Regulated Exocytosismentioning
confidence: 99%